Smaller prize, bigger size? Exploring the impact of money on men’s self-reported markers of masculinity - Christensen, Jacob Dalgaard; Otterbring, Tobias; Lagerkvist, Carl-Johan (Frontiers in Psychology, 2023)
Bodily markers, often self-reported, are frequently used in marketing research to predict consumption patterns. The present study examined whether men, at the aggregate level, would overestimate various markers of masculinity, and if so, to what extent. Furthermore, the study explored whether the amount of monetary rewards distributed to male participants would influence the obtained data quality. Men from two participant pools were asked to self-report a series of bodily measures. All self-report measures except weight were consistently found to be above the population mean (height and penis size) or the scale midpoint (athleticism). Additionally, the participant pool that received the lower (vs. higher) monetary reward showed a particularly powerful deviation from the population mean in penis size and were significantly more likely to report their erect and flaccid penis size to be larger than the claimed but not verified world record of 34 cm. These findings indicate that studies relying on men’s self-reported measures of certain body parts should be interpreted with great caution, but that higher monetary rewards seem to improve data quality slightly for such measures.